F. Dostojevskio „paslaptis" - Gaškienė-Červinskienė, E. (Literatūra, 1969)
The endeavour to reveal a man's „secret" - the essence of his spiritual life - is the invariable mark of Dostoevsky. The „secret" about Dostoevsky himself, his own principle idea, as stated in the article, is the idea of the freedom of personality. The writer remained faithful to it all his life long, despite the contradictoriness and evolution in his views. The idea as such seems to have sprung from Dostoevsky's very nature, as if comprising the inner make-up of his personality and determined the main peculiarities of his world outlook and his works.Attempts have been made to show how the author tries to bring his reactionary views into conformity with his democratic ideal of the freedom of personality by turning to religion. Attention has also been paid to the evolution of Dostoevsky's conception of the freedom of personality with regard to the changes in his views.